MODEL PEMBELAJARAN DISCOVERY LEARNING GAME GETS LUCKY CARD: STUDI ANALISIS PENINGKATAN PEMAHAMAN SISWA TERHADAP AL-QURAN - Puji Hastuti; Zaenal Arifin; Ajat Rukajat (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
LEARNING MODEL DISCOVERY LEARNING GETS LUCKY CARD GAME: IMPROVEMENT ANALYSIS STUDY STUDENTS' UNDERSTANDING OF THE AL-QURANThis study aims to improve understanding of student learning outcomes with the Discovery Learning (DL) learning model through the Games Gets Lucky Card method. The current globalization that has occurred recently has a very significant impact on the transformation of the world of education, especially in Indonesia, to a negative direction. The fast involvement of technology media also adds to the challenges and problems that are quite formidable to be faced by teachers in finding effective, efficient learning formulations that are liked by students at this time. The research method used is quantitative methods based on classroom action research. This research was carried out in two stages, each of which was based on planning, action, observation and reflection. Data collection was carried out using observation-based field study techniques where the research subjects were students and teachers at the MI Negeri Bekasi school. This study shows that the application of the Discovery Learning model can increase understanding activities and student learning outcomes in BTQ subjects. The research percentage shows that in the first cycle, the achievement of student learning activities was 68.62% which then increased in the second cycle to 96.10%. The increase in learning outcomes includes aspects of knowledge where the value obtained reaches an average of 77.63 and then these results increase so sharply in the implementation of cycle II with an average value of 87.95.